2014
DOI: 10.1371/journal.pone.0097193
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan Attenuates Colon Inflammation, Oxidative Perturbations and Apoptosis in a Rat Model of Experimental Inflammatory Bowel Disease

Abstract: Accumulating evidence has indicated the implication of angiotensin II in the pathogenesis of inflammatory bowel diseases (IBD) via its proinflammatory features. Telmisartan (TLM) is an angiotensin II receptor antagonist with marked anti-inflammatory and antioxidant actions that mediated its cardio-, reno- and hepatoprotective actions. However, its impact on IBD has not been previously explored. Thus, we aimed to investigate the potential alleviating effects of TLM in tri-nitrobenezene sulphonic acid (TNBS)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 58 publications
(129 reference statements)
5
100
1
3
Order By: Relevance
“…In animal models of IBD, DAI value and colonic length are key indicators for evaluating the severity of colitis [35, 36]. Consistent with the results of a previous study [17], SQE supplementation attenuated the severity of colitis by lowering the DAI value and extending the length of the colon.…”
Section: Discussionsupporting
confidence: 69%
“…In animal models of IBD, DAI value and colonic length are key indicators for evaluating the severity of colitis [35, 36]. Consistent with the results of a previous study [17], SQE supplementation attenuated the severity of colitis by lowering the DAI value and extending the length of the colon.…”
Section: Discussionsupporting
confidence: 69%
“…41 However, there is no effect of WJPs on the production of pro-inflammatory cytokines (TNF-α) in the macrophage. In this study, we demonstrated protection against colitis induced by TNBS in rats with WJPs treatment, exhibiting improved DAI scores, colon length, wet weight, histological damage and production of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited Inflammatory cell infiltration (mainly macrophages and neutrophils) during acute inflammation increases the formation of ROS and proinflammatory cytokines, such as TNF-α, IL-6, IL-1β, and inducible nitric oxide synthase (iNOS) (7,8). Overproduction of ROS, NO, and PGE2 leads to increased lipid peroxidation, decreased intestinal epithelial barrier integrity, and ultimately mucosal disruption and ulceration (9,10). Many immunogenic bacterial antigens from the damaged epithelial barrier enter submucosal layers and start a ruinous cascade of immune responses (11).…”
Section: Introductionmentioning
confidence: 99%